Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsami.9b01348
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cation Vacancies in Cu2SnSe3 Thermoelectrics

Abstract: In this study, a series of Cu2–x SnSe3 (x = 0.075–0.175) and Cu2Sn1–y Se3 (y = 0.06–0.1) compounds were synthesized by self-propagating high-temperature synthesis combined with plasma-activated sintering. The effects of different cation vacancies (Cu vacancies and Sn vacancies) on the thermoelectric properties are systematically studied. Both Cu vacancies and Sn vacancies enhance the carrier densities and move the Fermi level deeply into the valence band, promoting the multiband from Γ and S points involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
1
32
1
Order By: Relevance
“…The model samples produced by intentionally 8 depositing an oxyhydroxide phase on different supports suggests that perovskite-type oxides, which are ultimately able to build-up an active oxyhydroxide layer, are not barely a precursor of the active phase (the oxyhydroxide) but play also an essential role in boosting and sustaining the OER activity. [13] The same study also highlights the importance of the Fe presence in the self-assembled oxyhydroxide layer, being Co-or FeO(OH) catalysts much less active than the Co/FeO(OH) one. [13] Therefore, we have also carried out a systematic study to understand the functional role of Fe in perovskite OER catalysts with respect to activity and stability under operating conditions.…”
Section: Perovskite Oxides For the Electrochemical Water Splittingmentioning
confidence: 77%
See 2 more Smart Citations
“…The model samples produced by intentionally 8 depositing an oxyhydroxide phase on different supports suggests that perovskite-type oxides, which are ultimately able to build-up an active oxyhydroxide layer, are not barely a precursor of the active phase (the oxyhydroxide) but play also an essential role in boosting and sustaining the OER activity. [13] The same study also highlights the importance of the Fe presence in the self-assembled oxyhydroxide layer, being Co-or FeO(OH) catalysts much less active than the Co/FeO(OH) one. [13] Therefore, we have also carried out a systematic study to understand the functional role of Fe in perovskite OER catalysts with respect to activity and stability under operating conditions.…”
Section: Perovskite Oxides For the Electrochemical Water Splittingmentioning
confidence: 77%
“…[13] The same study also highlights the importance of the Fe presence in the self-assembled oxyhydroxide layer, being Co-or FeO(OH) catalysts much less active than the Co/FeO(OH) one. [13] Therefore, we have also carried out a systematic study to understand the functional role of Fe in perovskite OER catalysts with respect to activity and stability under operating conditions. [11c] In perovskite-type oxides as BSCF or LSCF, despite the fact that Fe constitutes only ⁓5 wt% of the mixed oxide, it greatly boosts both OER activity and stability performance.…”
Section: Perovskite Oxides For the Electrochemical Water Splittingmentioning
confidence: 77%
See 1 more Smart Citation
“…In accordance with the downshift Fermi level, the increased carrier concentration is observed and multiband around the downshift Fermi level can be involved in the electrical transportation. In Cu 2 Sn 0.93 Se 3 , ZT value of 0.87 is achieved at 800 K which is 67% higher than the pristine sample [63]. Except for moving the position of the Fermi level, the point defects may induce impurity levels contributing to an optimization of electrical [46].…”
Section: Sementioning
confidence: 91%
“…Previous studies on the band structure calculations have revealed that they have narrow band gap in the range 0.1-1.7 eV [4][5][6]. Various attempts have been done to enhance the TE performance via modifying electron and phonon transports through doping, non-stoichiometry and composites [1,[7][8][9]. Different methods like conventional solid-state reaction [8], fast combustion synthesis [10], liquid phase reactive sintering [6], spark plasma sintering [11], direct fusion of precursors [12], melt quenching [4] have been tried for synthesis of good quality bulk Cu 2 SnSe 3 polycrystalline materials.…”
Section: ∕2mentioning
confidence: 99%